DETERMINATION OF THE OPTIMUM CONDITIONS FOR BIOSURFACTANT PRODUCTION BY LOCAL ISOLATE OF LACTOBACILLUS PLANTARUM AND EVALUATE ITS ANTIMICROBIAL ACTIVITY - & Haider, Jameel (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Eighty five local isolates of Lactobacillus sp. which were isolated from different sources and identified by biochemical test then subjected to the primary and secondary screening processes to select the active Lactobacillus sp. isolate for biosurfactant production. Among the isolates screened, twenty six isolates with maximum for tests in primary screening were selected for secondary screening. It has been found that Lactobacillus sp. ADK2  had the highest productivity of the biosurfactant. The selected isolate with highest level of biosurfactant activity was identified as Lactobacillus plantarum ADK2 according to PCR technique. The optimum conditions of biosurfactant production by isolate Lactobacillus plantarum ADK2 using submerged fermentation were obtained in the synthetic mineral salt medium (MSM) and natural BCDFTM medium the best production medium separately, 1.5% (lactose and egg) as the best carbon source, 2% meat extract and 3.5% Pease as nitrogen source, temperature 30 °C for two media and pH 5 with pH 3 in MSM  and BCDFTM respectively, after 96 hr  and 72 hr in MSM and BCDFTM respectively of incubation period.